Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Guru Sekolah Minggu Buddha Se-DKI Jakarta - Riyadi Riyadi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
Educational institutions or schools are complex institutions. Teachers are educators who have a direct relationship with their students and therefore play a very large and important role in teaching and learning activities. Therefore, to produce quality students, teachers must have good performance. The performance of Buddhist Sunday School teachers can be declared successful if they have achieved the work target. Factors that can have an impact on the performance of Buddhist teachers include: how to practice organizational culture, teacher discipline when carrying out their duties, and the results achieved by teachers in carrying out their roles.